International Meetings of Photography. - Laoutliev, Nikolay; Plovdiv photographic foundation, Plovdiv (Antwerp : Project & Project, 2003)
Goiris, Geert ; Hanssen, Karin ; Danckaert, Bert ; Steculorum, Marc ; Boelens, Peter
On the occasion of the International Meetings of Photography, Annual Festival of photography, Plovdiv Bulgaria, October 2003
kunstcatalogus